2014
DOI: 10.1177/0192512114541562
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of ‘good citizenship’: A latent class analysis of adolescents’ citizenship norms in 38 countries

Abstract: Various authors have claimed that citizenship norms have changed dramatically in contemporary societies. Recent research has studied the implications of Russell Dalton's argument that dutybased citizenship norms (emphasizing voting and obeying the law) are being replaced by engaged citizenship norms (emphasizing self-expressive and non-institutionalized forms of participation). In this article we use the 2009 International Civic and Citizenship Education Survey (ICCS 2009, n=140,650) to ascertain the cross-nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 43 publications
11
99
1
8
Order By: Relevance
“…The largest group -'all-around citizens' represented roughly one third of the sample -perceived all behaviours to be important for being a good citizen, similar to 'respectful citizens' who were less positive about discussing politics though. Hooghe et al (2016) found strong variations of the group sizes across countries, and they showed that while higher status and lower political trust are associated with engaged norms of citizenship at the student level, engaged norms are not as prevalent in highly developed and stable democracies, questioning the generalizability of Dalton's thesis. Yet that research also suggested that engaged norms of citizenship might be on the rise, while an overall decline in duty-based norms was found among secondary school students between 1999 and 2009 (Hooghe & Oser, 2015).…”
Section: 'Good' Citizenship: Theoretical and Empirical Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…The largest group -'all-around citizens' represented roughly one third of the sample -perceived all behaviours to be important for being a good citizen, similar to 'respectful citizens' who were less positive about discussing politics though. Hooghe et al (2016) found strong variations of the group sizes across countries, and they showed that while higher status and lower political trust are associated with engaged norms of citizenship at the student level, engaged norms are not as prevalent in highly developed and stable democracies, questioning the generalizability of Dalton's thesis. Yet that research also suggested that engaged norms of citizenship might be on the rise, while an overall decline in duty-based norms was found among secondary school students between 1999 and 2009 (Hooghe & Oser, 2015).…”
Section: 'Good' Citizenship: Theoretical and Empirical Perspectivesmentioning
confidence: 98%
“…Although the concept of conventional citizenship is not exactly identical to what Dalton (2008) has labelled norms of civic duty, the distinction between a more traditional, conventional versus a more engaged, community-related understanding of citizen participation can be identified in all studies. In this connection, recent research utilized the ICCS database and employed latent class analysis, revealing five groups of students with distinct perceptions of good citizenship behaviours (Hooghe et al, 2016;Hooghe & Oser, 2015). Two of them were quite similar to what Dalton (2008) has described as engaged versus duty-based citizens, while a small minority showed low support for all citizenship norms and was labelled 'subjects,'…”
Section: 'Good' Citizenship: Theoretical and Empirical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However in their study of Swedish youth, they found four different types of citizenship orientations: traditionally active (high interest and high participation; however only 6% of their sample were of this type), standby (i.e., those with high interest but low participation; the largest group at 47%), unengaged (low interest and low participation; 26% were in the group), and disillusioned (also low interest and low participation but also dissatisfied and distrustful of political system; a large 21% were in this group) (Amnå and Ekman 2014). Subsequent research (Hooghe et al 2014;James 2012;Caren et al 2011;Raney and Berdahl 2009) has also found that engaged citizenship norms are not nearly as prevalent amongst the young as first reported by Dalton (2008), Zukin et al (2006) and others.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Til að mynda hefur vakið sérstaka athygli að ungmenni í grónum lýðraeðisríkjum telja ekki eins mikilvaegt og ungmenni í ungum lýðraeðisríkjum að þau sjálf séu virk í stjórnmálastarfi, þ. á m. kosningum (Torney-Purta & Amadeo 2003). Þrátt fyrir þetta bendir þó ýmislegt til þess að ungt fólk hafi áhuga á tilteknum samfélagsmálum, eins og jafnréttismálum, og að vernda mannréttindi og umhverfið (Hooghe, Oser & Marien 2016). Kosningaþátttaka ungs fólks segir því ekki alla söguna um virkni unga fólksins sem samfélagsborgara.…”
Section: Inngangurunclassified